Power Conversion System for Hybrid Battery-Capacitor Storage - Serna-Garcés, Sergio Ignacio; Ramos-Paja, Carlos Andrés; Gonzalez-Montoya, Daniel (Ingeniería, 2020)
Context: Thanks to the low emissions of CO2 generated by electric systems, those solutions have an increased attention from industry and academia. However, the electrical storage systems required in a large amount of applications must to have both high energy and power densities. Method: To meet those requirements, this paper proposes an active hybrid energy storage system (HESS), which is formed by a battery, i.e. the device with high energy density, and a capacitor, i.e. the device with high power capability. The proposed power system also protects the battery by limiting the current derivative. Results: Two sliding-mode controllers (SMC) are designed to regulate both the battery current and the load voltage. The design process guarantees the global stability and safe battery operation. Conclusions: The controller avoids the battery degradation caused by the high-frequency current components since the capacitor assumes those components demanded by the load profile.